Síndrome aguda do tórax como primeira manifestação de anemia falciforme em adulto - Yoo, Hugo Hyung Bok [UNESP]; Pelegrino, Nilva Regina [UNESP]; Carlos, Ana Lúcia Oliveira De [UNESP]; Godoy, Irma De [UNESP]; Queluz, Thais Thomaz [UNESP] (Sociedade Brasileira de Pneumologia e Tisiologia, 2002)
Acute chest syndrome is an affection, specially in young adults, of sickle cell disease and is responsible for 25% of the deaths. The authors report the case of an alcoholic 45-year-old mulatto man, without any previous manifestation of sickle cell disease, who presented with a pneumonia-like clinical picture with seven days of duration. The chest X-ray revealed bilateral lung infiltrates and spots of consolidation with air bronchograms, and left pleural effusion. The patient also had anemia and leukocytosis with neutrophilia. Treated with cefoxitin and amicacin, the patient developed acute respiratory insufficiency and died 14 hours after hospitalization. The necropsy showed lungs with intense congestion, intra-alveolar hemorrhage, diffuse alveolar damage, and sickle red blood cells. The progressive, fast, and severe character of the acute chest syndrome, which is frequently mimicked by other illnesses, makes the disease a dramatic and severe event of difficult earlier diagnosis. Therefore, in countries like Brazil, with a large black population, the physicians must always be aware of this possibility.

A síndrome aguda do tórax (SAT) acomete portadores de anemia falciforme e é responsável por cerca de 25% dos óbitos. Relata-se o caso de um homem pardo de 45 anos, alcoolista crônico, sem nenhum antecedente de falcização, com quadro de pneumonia-símile havia sete dias. A radiografia simples do tórax mostrou infiltrado heterogêneo bilateral, com áreas de consolidação e broncograma aéreo e derrame pleural à esquerda. Outros exames laboratoriais revelaram anemia, leucocitose com desvio à esquerda e hipoxemia. Tratado com cefoxitina e amicacina, o paciente evoluiu rapidamente para insuficiência respiratória aguda e morreu 14 horas após a internação. Na necropsia, no exame dos pulmões observaram-se intensa congestão, hemorragia intra-alveolar, dano alveolar difuso e hemácias com morfologia falciforme. O caráter rápido, progressivo e freqüentemente mimetizado por outras doenças torna a SAT um evento dramático e de diagnóstico precoce difícil, sendo, entretanto, obrigatória tê-la sempre em mente, especialmente em um país com grande população da raça negra como o Brasil.
Acute chest syndrome as the first manifestation of sickle cell disease in a middle aged adult
Keywords: Pneumonia; Sickle cell anemia; Diagnosis; Pneumonia; Anemia falciforme; Diagnóstico